Impact of Dry Eye Syndrome on Vision-Related Quality of Life in a Non-Clinic-Based General Population - Le Qihua (BMC Ophthalmology, 2012)
Abstract Background Dry eye syndrome (DES) is a common ocular disorder occurring in general population. The purpose of this study is to evaluate the impact of DES on vision-related quality of life (QoL) in a non-clinic-based general population. Methods This population-based cross-sectional study enrolled subjects older than 40 years, who took part in an epidemiological study on dry eye in Sanle Community, Shanghai. Apart from the collection of sociodemographics, dry eye symptoms, and other clinical data, a Chinese version of the 25-item National Eye Institute Visual Functioning Questionnaire (NEI VFQ-25) was administered to all subjects. Comparisons of the NEI VFQ-25 subscale item scores and composite score were made among subgroups divided according to the presence of dry eye symptoms or signs. Multivariate regression analysis was performed to investigate the relationship between the clinical variables and the VFQ-25 composite score. Results A total of 229 participants were enrolled in the study, with an average age of (60.7 ±10.1) years old. Majority of these participants were female (59.8 %, 137/229). The total DES symptom scores (TDSS) in subjects either with definite DES or only with dry eye symptoms were significantly higher (F = 60.331, P < 0.001). The values of tear break-up time (TBUT) and Schirmer test were significantly lower in participants with DES and those with dry eye signs only (F = 55.158 and 40.778, P < 0.001). The composite score of the NEI VFQ-25 was significantly lower in subjects with DES (F = 4.901, P = 0.003). Moreover, the subscale scores of ocular pain and mental health were significantly lower in those with either DES or dry eye symptoms only (F = 10.962 and 7.362 respectively, both P < 0.001). The multiple regression analysis showed that the TDSS had a significant negative correlation with the VFQ-25 composite score as well as with the subscale score for ocular pain and mental health, even after the adjustment of all other factors (all P < 0.01). Conclusions The symptoms of dry eye are associated with an adverse impact on vision-related QoL in non-clinic-based general population, which is mainly represented as more ocular pain and discomfort, and impaired mental health as well. Apart from clinical examination, it is also important to refer to subjective symptoms and QoL scores when assessing the severity of DES.